FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA PEGAWAI DINAS KEBERSIHAN DAN PERTAMANAN (DKP) KOTA SAMARINDA - Elfreda Aplonia Lau 3, WAHYUDI RIZAL LCA. Robin Jonathan2 (EKONOMIA, 2016)
WAHYUDI RIZAL, "Factors Influencing Employee Performance Against and Sanitation Department (DKP) Samarinda City", led by Mr. LCA.Robin Jonathan, as a mentor I, and Mrs. Elfreda a.Lau, as a mentor II.The purpose of this study was to determine the influence of Style Leadership, Education and Training, and Work Discipline motovasi on employee performance and Sanitation Department (DKP) Samarinda. Model analysis used to prove the hypothesis is multiple linear regression analysis model with the number of respondents 58 employees on Factors Influencing Employee Performance Against and Sanitation Department (DKP) Samarinda.Statistical analysis showed regression coefficient of variable-free variable, namely Leadership Style (X1) = 0.100, Education and Training (X2) = 0.036, Working Environment (X3) = - 0.204, work motivation (X4) = 0.148 and the Discipline of Work (X5 ) = 0.744 and -1.077 of the constants of this value gerganda linear regression equation is:Y = 0.358 + 0,1X1 + 0,347X2 + (- 0,204X3 + 0,148X4 + 0,744X5)From the results obtained by analysis of the correlation coefficient R of 0.707, which means jointly variable Leadership Style (X1), Education and Training (X2), Working Environment (X3), work motivation (X4) and Work Discipline (X5) have a relationship strong on the performance of employees at the Department of Hygiene and (DKP) Samarinda.It is shown from the results of the determinant coefficient (R2) of 0.562, which means that the performance of employees at the Department of Hygiene and (DKP) Samarinda, influenced by variable Leadership Style (X1), Education and Training (X2), Working Environment (X3), Work Motivation (X4) and Work Discipline (X5).The results of this study indicate that all independent variables simultaneously have a significant influence on the performance of employees at the Department of Hygiene and (DKP) Samarinda., Style Pepemimpinan insignificant because less effect on performance, education and training have a significant effect because it plays an important role, Work Environment is not significant because it does not affect performance, motivation is not significant because it is less contributes to performance, while the Work Discipline sifnifikan effect on performance due to increases in employee performance and Sanitation Department (DKP) Samarinda